Hypoxia Induces Oxidative Injury and Apoptosis via Mediating the Nrf-2/Hippo Pathway in Blood Cells of Largemouth Bass (Micropterus salmoides) - Xin, Yu; Yang, Zhixin; Zhu, Yuke; Li, Yixuan; Yu, Jie; Zhong, Wanqing; Chen, Yanhan; Lv, Xiaohui; Hu, Junru; Lin, Jinjiang; Miao, Yutao; Wang, Lei (Frontiers in Ecology and Evolution, 2022)
Investigating how aquatic animals respond to hypoxia brought about by changes in environmental temperature may be of great significance to avoid oxidative injury and maintain the quality of farmed fish in the background of global warming. Here, we investigated the effects of hypoxia on oxidative injury and environment-sensing pathway in blood cells of Micropterus salmoides. The total blood cell count (TBCC) and Giemsa staining showed that hypoxia could lead to damage and apoptosis of blood cells. Flow cytometry analysis showed that the apoptosis rate, Ca2+ level, NO production and ROS of blood cells of Micropterus salmoides were significantly increased under hypoxia stress. Environment-sensing pathways, such as Nrf2 pathway showed that hypoxia resulted in significant up-regulation of hiF-1 alpha subunit (Hif-1α), nuclear factor erythroid 2-related factor 2 (Nrf2) and kelch-1ike ECH- associated protein l (Keap1) expression. Meanwhile, Hippo pathway-related genes such as MOB kinase activator 1 (MOB1), large tumor suppressor homolog 1/2 (Lats1/2), yes-associated protein /transcriptional co-activator with PDZ-binding motif (YAP/TAZ), protein phosphatase 2A (PP2A) were significantly increased in blood cell after hypoxia exposure. In addition, hypoxia stress also increased the expression of catalase (CAT) and glutathione peroxidase (GPx), but decreased the expression of superoxide dismutase (SOD). Consequently, our results suggested that hypoxia can induce oxidative injury and apoptosis via mediating environment-sensing pathway such as Nrf2/Hippo pathway in blood cells of Micropterus salmoides.